Analisis Pengelolaan Keuangan Syariah Pedagang Sayur Wanita di Pasar Muara Tembesi - Dilla Pinanti; Efni Anita; Rohana Rohana (Pusat Riset dan Inovasi Nasional, 2025)
One of the human activities in meeting daily needs requires a market as a means of support. The market will progress if financial management runs well, but on the other hand, if management does not run well it will result in losses, both in the market and for its partners. This article aims to analyze the knowledge of Vegetable Trader entrepreneurs and how they practice Sharia financial management in the businesses they run. This research was carried out at the Muara Tembesi Market directly and freely using descriptive qualitative research, namely direct interviews conducted in a relaxed manner, without complicating the informants, and the questions asked were not of an interrogative nature but only to obtain the data needed to complete and complete the writing in this research. The research results show Sharia financial management. Using a phenomenological approach, this research observed 15 informants who were vegetable traders at Muara Tembesi Market. The results of this research prove that all informants have knowledge of the concept of Islamic or Sharia financial management. Entrepreneurs have also implemented Islamic financial management through allocating budgets for zakat, infaq and alms. Apart from that, business actors also have savings and investment funds for their businesses. However, the majority of entrepreneurs still implement simple financial management. Regarding budgeting, financial reports and cash management have not been implemented in a structured manner.